Pengembangan Kurikulum Berbasis Keterampilan Abad Ke-21 untuk Sekolah Dasar - Muhammad Hafiz; Abdul Rashid Abdul Aziz; Haji Hamli (PT. Global Pustaka Ilmiah, 2024)
The development of a 21st century skills-based curriculum for elementary schools is becoming increasingly important in the context of modern education. The importance of developing a 21st century skills-based curriculum is to ensure that education can provide maximum benefits for student development. This study aims to describe the impact of developing a 21st century skills-based curriculum on academic achievement and student readiness to face future challenges. The method used in this study is a qualitative method with a type of library research. The results of the study indicate that the development of a 21st century skills-based curriculum for elementary schools aims to prepare students with skills that are relevant and needed in the modern era. This curriculum also emphasizes the development of skills such as communication skills, collaboration skills, critical skills, digital literacy skills, entrepreneurship skills, lifelong learning skills. With changes in the curriculum, teachers and students must adapt to the new curriculum. This skills-based curriculum also encourages more interactive, contextual, and relevant learning.